Efektivitas Penggunaan Kombinasi Media Tanam Organik Terhadap Pertumbuhan Vegetatif Tanaman Cabai Rawit (Capsium frutescens) - anugrah, devi (Al-Nafis: Jurnal Biologi dan Pendidikan Biologi, 2023)
One of the supports for the successful growth of cayenne pepper plants (Capsicum frutescens) is a planting medium that is rich in nutrients. Organic planting media comes from organic ingredients which contain nutrients and are able to balance air circulation and high water absorption. This study aims to determine the effectiveness of the combination of organic growing media used on the growth of cayenne pepper (Capsicum frutescens). This research was conducted in the greenhouse of FKIP UHAMKA, East Jakarta in February - May 2023. This research used a quantitative experimental method with a completely randomized design (CRD). This study used 4 treatments with 5 replications each, the factors observed consisted of control treatment P0 (100% soil), P1 (50% soil: 25% husk charcoal: 25% cocopeat), P2 (50 % soil : 25% husk charcoal : 25% raw husk), and P3 (50% soil : 25% husk charcoal : 25% manure. The research data were analyzed using the One-Way ANOVA test and if they were significantly different then a ‎test was carried out Duncon continued the Multiple Range Test (DMRT). For the best results on the parameters of plant height and plant wet weight found in the P3 treatment with a combination of soil planting medium, husk charcoal, and manure, obtaining an average plant height of 6.48 cm and wet weight of 0.22 gr. The best root length parameter was treatment P2 with a combination of soil, rice husk charcoal, and raw husks with an average of 3.78 cm. The results of the One-Way ANOVA test were not There was a significant difference in each treatment, meaning there was no difference to the control treatment